Pengaruh Modal Usaha, Karakteristik Wirausahawan dan Orientasi Kewirausahaan Terhadap Kinerja Usaha Kedai Kopi - Wahyu Bintang Pangestu; Muhammad Fikry Aransyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine whether there is an influence of venture capital, entrepreneurial characteristics, and entrepreneurial orientation on the performance of coffee shop businesses in North Bontang District. This research is a quantitative research. Where in the collection of research data using a questionnaire distributed to respondents. For the number of samples themselves as many as 30 respondents with a purposive sampling method with the criteria of a coffee shop that has been operating for at least 1 year. Primary data is the data used in this study. Questionnaires will be a technique in collecting data used in this study. The data analysis techniques used in this study are validity and reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the venture capital variable partially has a positive and significant effect on business performance. Likewise with the variable characteristics of entrepreneurs, based on the output of SPSS, it is found that the variable of entrepreneurial characteristics has a positive and significant effect on business performance. Meanwhile, the entrepreneurial orientation variable has a negative effect on the performance of the coffee shop business in North Bontang District. From the results of SPSS output, it can be seen that the value of Adjusted R Square is 0.533 or 53.3%, which is 46.7% which can be interpreted as being explained by other variables not included in this model.